PENGARUH WORKING CAPITAL MANAGEMENT TERHADAP PROFITABILITAS PERUSAHAAN FARMASI YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) PERIODE 2009-2013 - AYU LARASWATI, ELIZABETH (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACT This study aimed to determaine the effect of working capital management on the profitability of pharmacy companies in Indonesia. This paper used secondary data pharmacy companies listed in Indonesia Stock exchange the period 2009-2013. This reserach uses a regression analysis. Working capital is measured through the working capital turnover (WCT) also used current ratio (CR) and debt to total equity (DTE) as othe independent variable. The result showed that the working capital turnover (WCT) and debt to total equity have no significant effect on profitability. While, current ratio have significant influence in the profitability of the company. Keywords: Working Capital Turnover, Current Ratio, and Debt To Total Equity